2014
DOI: 10.1089/scd.2014.0058
|View full text |Cite
|
Sign up to set email alerts
|

Pax6 Is Essential for the Maintenance and Multi-Lineage Differentiation of Neural Stem Cells, and for Neuronal Incorporation into the Adult Olfactory Bulb

Abstract: The paired type homeobox 6 (Pax6) transcription factor (TF) regulates multiple aspects of neural stem cell (NSC) and neuron development in the embryonic central nervous system. However, less is known about the role of Pax6 in the maintenance and differentiation of adult NSCs and in adult neurogenesis. Using the + /Sey Dey mouse, we have analyzed how Pax6 heterozygosis influences the self-renewal and proliferation of adult olfactory bulb stem cells (aOBSCs). In addition, we assessed its influence on neural diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 80 publications
0
32
0
Order By: Relevance
“…Notably, the subset of genes that all three studies agreed were downregulated comprised a DAVID cluster involved in patterning, cell migration and urogenital development. This group included GREM1 , DUSP6 , CAV1 , and SFRP1 , which are involved in MAP kinase, BMP, and Wnt signaling , as well as SOX17 , LHX1 , STMN2 , PAX6 , and LIN7a , which are involved in differentiation .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the subset of genes that all three studies agreed were downregulated comprised a DAVID cluster involved in patterning, cell migration and urogenital development. This group included GREM1 , DUSP6 , CAV1 , and SFRP1 , which are involved in MAP kinase, BMP, and Wnt signaling , as well as SOX17 , LHX1 , STMN2 , PAX6 , and LIN7a , which are involved in differentiation .…”
Section: Resultsmentioning
confidence: 99%
“…It is also now increasingly appreciated that gene regulatory programs launched early in fetal life to specify neuronal‐type identities, continue to function later in life to maintain postmitotic identities . Indeed, animal models have demonstrated the persistence of Pax6 expression, and its role in the generation of neural stem progenitor cells and maintenance of neurogenic fate in the adult rodent brain. Ninkovic et al demonstrated that ongoing expression of Pax6 in mature healthy brain is intrinsically required for the survival of dopaminergic neurons in the olfactory bulb through maintenance of crystalline α A expression, which prevents caspase‐3‐mediated programmed cell death .…”
Section: Discussionmentioning
confidence: 99%
“…After six DIV the cells were recovered for RNA extraction followed by real‐time reverse transcription quantitative‐polymerase chain reaction (RT‐qPCR) analysis using the primers listed in Supporting Information Table S3. Then, gene expression changes Igf‐I Δ/Δ mice were compared relative to the levels of gene expression obtained in Igf‐I Ctrl mice, using the CT method and were expressed as fold changes in log2 scale. The expression of Igf‐I in HPSCs, olfactory bulb stem cells (OBSCs), fibroblasts and hepatocytes obtained from Igf‐I Ctrl and Igf‐I Δ/Δ mice was also measured by (RT‐qPCR) and the results were given as relative mRNA levels normalized to the Ct value for Gapdh .…”
Section: Methodsmentioning
confidence: 99%